Invasion of lymphatic vessels into the eye after open globe injuries - Wessel, Julia M.; Hofmann-Rummelt, Carmen; Kruse, Friedrich; Cursiefen, Claus; Heindl, Ludwig M. (Investigative Ophthalmology & Visual Science, 2012)
We analyzed whether lymphatic vessels can be detected in eyes enucleated after an open globe injury.The presence of lymphatic vessels was analyzed immunohistochemically using podoplanin as a specific lymphatic endothelial marker in 21 globes that had been enucleated after open globe injury. The localization of pathologic lymphatic vessels (within the eye wall or inside the eye) was correlated with the mechanism of trauma, anatomic site of perforation or rupture, and time interval between trauma and enucleation.Pathologic lymphatic vessels were detected in 15 of 21 eyes (71%) enucleated after an open globe injury. In 5 globes (24%) they were found within the eye, located in retrocorneal membranes, underneath the sclera, and adjacent to uveal tissue (ciliary body, iris). No significant association was observed between the presence of pathologic lymphatic vessels and the mechanism of trauma (P = 0.598), anatomic site of perforation or rupture (P = 0.303), and time interval between trauma and enucleation (P = 0.145).The human eye can be invaded secondarily by lymphatic vessels if the eye wall is opened by trauma. This mechanism could be important for wound healing, immunologic defense against intruding microorganisms, and autoimmune reactions against intraocular antigens.
EVALuna2:21111